Growth and nutrient uptake of Roselle (Hibiscus sabdariffa) with the application of organic and inorganic fertilisers - Muhammad Firdaus Suraimi; Muhammad Nazri Abdul Talib; Irma Noorazurah Mohamad; Nur Syahiza Zainuddin; Nurhidayah Hamzah; Marfiah Ab Wahid; Mohd Zuraidi Komari; Zulhailmy Mohd Yatim (Penerbit Universiti Kebangsaan Malaysia, 2024)
Composting is a sustainable practice that uses the organic waste as the nutrient-rich compost, which offers numerous benefits in agriculture while improving soil fertility and enhances plant growth. Organic fertilisers are increasingly recognized for their potential to enhance crops productivity while at the same time have less impacts towards the environment. The aim for this study was to evaluate the effects on the different application of fertilisers on the growth and yield of the Roselle plant (Hibiscus sabdariffa) by evaluating on the plant growth parameters. This study is focused on the plant growth and determination of nitrogen (N), phosphorus (P) and potassium (K) uptake of the plant. The plants were divided into four (4) different treatments with one being the control. Among the plant growth metrics examined in this study are plant height, leaf count, and Roselle yield. After 49 days of observation, the plant height averaged at 178 mm, with 16 leaves produced across all treatments. Roselle that grown under combination of soil, fertiliser with compost (P3), and soil with fertiliser only (P4) produced the most number of fruit (8 fruits/plant). In addition, the highest leaves count (45 leaves/plant) contributed from Roselle under soil with fertiliser only (P4). It is observed that the Roselle with organic fertiliser treatment have low significant improvement in plant growth as compared to the plants in other treatments. The findings of this study showed that food waste can be applied in composting to promote plant growth ecologically responsible farming practices and improve plant development and output. The benefits of compost may be more noticeable over a longer period and in combination with other soil management practices.